IMPROVING TEACHERS' ABILITY TO DEVELOP INDEPENDENT CURRICULUM TEACHING MODULES THROUGH TRAINING BY SCHOOL SUPERVISORS AT SMK NEGERI 3 TABANAN - Dewa Made Wardika Yusana (Indonesian Journal of Educational Development (IJED), 2023)
Teachers must be able to plan hands-on lessons in a way that encourages fun, creative, and engaging learning. The research objective was to improve the ability of SMK Negeri 3 Tabanan teachers to develop teaching modules. The results of the supervision and evaluation carried out on the teachers of SMK Negeri 3 Tabanan show that most of the teachers have not been able to develop teaching modules independently, so anticipatory action is needed. This research is a school action research. School Action Research is a type of self-reflection carried out by educational actors in the educational environment to improve the quality of education, understanding of these practices, and the conditions for their implementation. The research was done at SMK Negeri 3 Tabanan both online and offline. The Study took place in 2022 between July and August. A total of 86 teachers of SMK Negeri 3 Tabanan participated in this study. Based on the research findings, supervising coaching has the potential to improve teachers' ability to create Independent Curriculum Teaching Modules through training. One indicator of the success of school action research is that 100% of teachers are very good at making Independent Curriculum Teaching Modules.